Atlantic salmon (Salmo salar) parr as a model to predict the optimum inclusion of air classified faba bean protein concentrate in feeds for seawater salmon - De Santis, Christian; Ruohonen, Kari; Tocher, Douglas R; Martin, Sam A M; Krol, Ella; Secombes, Christopher J; Bell, J Gordon; El-Mowafi, Adel; Crampton, Viv (Aquaculture, 2015)
The limited availability of marine ingredients means that new and improved raw materials with high potential to replace fishmeal (FM) are required. Faba bean (Vicia faba) is a legume with good potential that has previously been tested in fish species with some promising results. The present study aimed to determine whether an air-classified faba bean protein concentrate (BPC, 615 g kg-1 crude protein content) could offer improved or favourable growth performance and physiological responses compared to the main commercially used protein sources, FM and soy protein concentrate (SPC), in Atlantic salmon (Salmo salar). The trial investigated the performance of 16 feeds formulated with varying FM/SPC/BPC proportions using a mixture design approach. Salmon parr of average weight 1.47 g were used as a model. The trial lasted eight weeks and also included high FM (560 g kg-1) and high defatted soybean meal (360 g kg-1) feeds as negative and positive controls respectively, for the assessment of gut inflammation. The results demonstrated conclusively that total inclusion levels of BPC ranging from 50 to 200 g kg-1, partially replacing SPC and/or FM, displayed the greatest potential to be beneficial in terms of fish performance and nutrient composition with increased growth, protein content, fat content and ash. In addition to favourable whole-body composition parameters, it was found that inclusions of BPC below 340 g kg-1 of feed did not cause detrimental effects such as the gut inflammation observed in fish fed the high soybean meal control. High Inclusion level (450 g kg-1) of BPC caused a mild gut inflammation that was not as severe as that caused by the feed with high soybean meal. The results of this screening study indicate that BPC derived from faba beans can be a valuable alternative protein source in Atlantic salmon feeds. The data provided a platform to model the optimum range of BPC inclusion levels in combination with FM and SPC for further investigation in commercially relevant fish and conditions.